Financial and Monetary Reforms and the Finance-Growth Relationship in Zimbabwe - Tyavambiza, Takawira; Nyangara, Davis (International Journal of Economics and Financial Issues, 2015)
The study employs the Granger causality test in a multivariate cointegration and error correction environment to examine the relationship between financial development and economic growth in Zimbabwe. Using annual data from 1980 to 2012, and after controlling for financial and monetary reforms, the study demonstrates a unidirectional causal relationship that runs from financial development to economic growth. The evidence shows that financial development; banking sector development in particular, is not a passive response to economic growth. Instead, it is a critical tool for accelerating economic growth. Policy implications of this evidence are that the banking sector in Zimbabwe must be supported with policies that encourage credit expansion and innovation to support economic growth. The equities market, on the other hand, requires more investor-friendly innovations and policies, especially with regard to trading efficiency and foreign investor participation in the primary market. In combination, these policy interventions should be able to magnify the positive effect of financial development on economic growth. Keywords: Financial development; economic growth; financial reforms; Granger causality. JEL Classifications: C22; E44; G10; O11; O40